Real-world effectiveness and safety of first-line chemoimmunotherapy combinations in metastatic non-small cell lung cancer with programmed death ligand-1 < 50%: results from an Italian observational study - Alessandro Inno; Antonello Veccia; Ettore D’Argento; Floriana Morgillo; Elio Gregory Pizzutilo; Fabiana Vitiello; Alberto Pavan; Fiorella Lombardo; Marco Russano; Vincenzo Sforza; Francesca Colamartini; Carlo Genova; et al. (Cancer Immunology, Immunotherapy)
Abstract Introduction This multi-center, observational cohort study aimed to evaluate the real-world effectiveness and safety of two first-line chemoimmunotherapy combinations—pembrolizumab plus chemotherapy and nivolumab/ipilimumab plus chemotherapy—in patients with metastatic non-small cell lung cancer (NSCLC) and programmed death ligand-1 (PD-L1) expression < 50%. Patients and Methods The primary objectives were progression-free survival (PFS) and overall survival (OS) in the overall population. Secondary objectives included the incidence of chemotherapy-related and immune-related adverse events (irAEs). Results A total of 495 patients were enrolled, with 348 (70.3%) receiving pembrolizumab plus chemotherapy and 147 (29.7%) treated with nivolumab/ipilimumab plus chemotherapy. Overall, median follow-up was 11 (95% CI: 10.2 12.2) months. The median PFS was 10.9 months (95% CI: 9.6–13), and the median OS was 21.1 months (95% CI: 16.8–NR) in the overall population. In multivariable analysis, ECOG PS ≥ 2, PD-L1 expression < 1%, squamous histology, baseline steroid use, and the presence of CNS, bone, or liver metastases were significantly associated with shorter survival. No significant differences were observed between the pembrolizumab and nivolumab/ipilimumab cohorts in terms of PFS (11.83 vs. 9.83 months; HR 0.86, 95% CI: 0.67–1.11, p = 0.3) or OS (21.3 vs. 20.6 months; HR 1.03, 95% CI: 0.76–1.39, p = 0.9). Chemotherapy-related adverse events were more frequent in the pembrolizumab cohort, whereas irAEs were more common in the nivolumab/ipilimumab cohort. Conclusion In this real-world study, chemoimmunotherapy combinations demonstrated manageable toxicity profiles, with effectiveness comparable to that reported in pivotal phase 3 randomized trials. Pembrolizumab and nivolumab/ipilimumab showed similar real-world effectiveness but significantly different toxicity profiles.